2018
DOI: 10.1016/j.cellsig.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-kinase p110α negatively regulates thrombopoietin-mediated platelet activation and thrombus formation

Abstract: Phosphoinositide 3-kinase (PI3K) plays an important role in platelet function and contributes to platelet hyperreactivity induced by elevated levels of circulating peptide hormones, including thrombopoietin (TPO). Previous work established an important role for the PI3K isoform; p110β in platelet function, however the role of p110α is still largely unexplored. Here we sought to investigate the role of p110α in TPO-mediated hyperactivity by using a conditional p110α knockout (KO) murine model in conjunction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 55 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…In addition, it has been reported that pharmacologic inhibition of PI3Kα contributes to suppression of insulin-like growth factor-1 (IGF-1) induced AKT activation, inhibition of platelet activation and thrombus formation in cultured human platelets [ 37 ]. In a closer inspection, another study showed that PI3Kα inhibition augments thrombopoietin-mediated platelet activation and thrombus formation through restricting thromboxane A2 synthesis and extracellular signal-regulated kinase (ERK) phosphorylation [ 38 ]. Additionally, loureirin, a flavonoid extracted from dragon’s blood (a deep red resin secreted from Dracaena ), has been shown to suppress platelet activation through PI3K/AKT signaling pathway inhibition [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that pharmacologic inhibition of PI3Kα contributes to suppression of insulin-like growth factor-1 (IGF-1) induced AKT activation, inhibition of platelet activation and thrombus formation in cultured human platelets [ 37 ]. In a closer inspection, another study showed that PI3Kα inhibition augments thrombopoietin-mediated platelet activation and thrombus formation through restricting thromboxane A2 synthesis and extracellular signal-regulated kinase (ERK) phosphorylation [ 38 ]. Additionally, loureirin, a flavonoid extracted from dragon’s blood (a deep red resin secreted from Dracaena ), has been shown to suppress platelet activation through PI3K/AKT signaling pathway inhibition [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…TxA 2 generation was assessed by measuring TxB 2 in platelet supernatants using a commercially available colorimetric ELISA kit (Enzo Life Sciences, Exeter, UK) as previously described [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…7,8 The phenomenon of COVID-19 platelet activation is likely due to the association between inflammation/infection and platelet production. Platelet production and activation is driven by thrombopoietin, 9,10 which is upregulated by inflammatory cytokines activated in COVID-19 infection, such as interleukin-6. Platelets also possess cell surface receptors that contribute to immune cell interaction and function.…”
mentioning
confidence: 99%